PHYTOCHEMICAL SCREENING AND in vitro ANTIOXIDANT PROPERTIES OF persea americana SEED GROWN IN NNEWI, SOUTH EASTERN NIGERIA (Journal of Biomedical Investigation, 2024)
Background: Persea americana (avocado) is a popular plant that has been used traditionally for its nutritional and medicinal values. The efficacy of a medicinal plant is contingent upon the bioactive compounds it possesses.Aim: The study investigated the phytochemical and in vitro antioxidant properties of the ethanolic seed extract of P. americana obtained from rural part of Nnewi, Anambra State, Nigeria.Methodology: The dried pulverized seeds of P. americana were extracted with ethanol by the maceration method. The extract obtained was subjected to phytochemical screening. In vitro antioxidant assays, (2,2’-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and ferric reducing antioxidant properties (FRAP) were also carried out on the extract.Results: The phytochemical screening of the extract revealed the presence of flavonoids, saponins, alkaloids, tannins, glycosides, steroids and oxalate. Kaempferol, a flavonoid was found to be the predominant phytochemical compound (50.890±0.002 µg/ml). The extract showed a higher DPPH scavenging activity than the ascorbic acid standard at lower concentrations. The DPPH activity was highest (91.61±0.10 %) at concentration of 31.5 mg/ml. The extract also showed a concentration-dependent increase in FRAP activity, and was found to have a higher activity than the reference antioxidant, ascorbic acid.Conclusion: This study revealed that the plant seed contains substantial amount of hydroxyl radical scavenging, and ferric reducing power activity, and could be a source of naturally occurring antioxidants that is beneficial to health.
Keywords: Persea americana; Flavonoids; Free radicals; Antioxidants; Medicinal plants